Edukasi Mutu Pelayanan Kesehatan Berbasis Dimensi Servqual untuk Meningkatkan Kepuasan Pasien di Puskesmas Suralaga Lombok Timur - Nelly Nurzanty (Fakultas Teknik Universitas Cenderawasih, 2026)
This community service activity aims to improve health workers’ understanding and implementation of service quality based on the SERVQUAL dimensions, including tangible, reliability, responsiveness, assurance, and empathy, at Puskesmas Suralaga, East Lombok, while increasing patient awareness regarding their rights to receive quality health services. The activity involved 28 health workers and 45 patients and was conducted through situational analysis, coordination with Puskesmas management, health education sessions, service simulations, and evaluation using pre- and post-activity questionnaires. The results indicated an improvement in health workers’ average understanding of service quality standards from 62.4 to 84.7 on a 100-point scale. In addition, the patient satisfaction index increased from 68.1% (fairly satisfied) to 85.6% (satisfied) across all SERVQUAL dimensions, with the most significant improvements found in responsiveness and empathy. These findings indicate that participatory and structured service-quality education can effectively enhance health workers’ competencies and patient satisfaction. This approach provides a practical, affordable, and sustainable strategy for strengthening the quality of primary health care services at the Puskesmas level.